Pengaruh Gerakan Literasi Sekolah Terhadap Peningkatan Literasi Digital Siswa di SMPN 1 Tompobulu Kabupaten Gowa - Fitriani, Sri; Muliyadi, Irvan; Ramadayanti, Ramadayanti (Literatify : Trends in Library Developments, 2021)
This study aims to determine the effect of the school literacy movement on increasing students’ digital literacy at SMPN 1 Tompobulu, Gowa district. This study uses a quantitative descriptive research located at SMPN 1 Tompobulu, Gowa Regency. The source of data in this study is primary data, namely the method of data collection using a questionnaire method distributed to all students at SMPN 1 Tompobulu, Gowa district. The number of samples used were 81 respondents, with primary data processing using analytical techniques with the help of SPSS statistical software version 22. The results of this study indicate that the school literacy movement has a positive and significant effect on increasing students’ digital literacy at SMPN 1 Tompobulu, Gowa Regency by 0.811 or 81.1% while the remaining 18.9% is explained by other variables not examined in this study. . School literacy activities are complex in shaping the ability of students at SMPN 1 Tompobulu to start thinking analytically, systematically, evaluatively, critically, imaginatively and creatively so that the implementation of digital literacy is considered a very important part in the activities of the school literacy movement.